Connecting the chain: Value-chain linkages, governance and market power in Tanzania’s sunflower sub-sector - Baltazar Namwata (Journal of Sustainable Community Development, 2026)
This paper maps the sunflower value chain in Central Tanzania and analyses how linkages, governance arrangements, and market power shape the participation of farmers, processors, traders, consumers, and support institutions. The study used evidence from a mixed-methods value-chain survey conducted in Kondoa, Mpwapwa, Manyoni, and Singida districts. Quantitative data from 379 respondents were analysed using descriptive statistics, cross-tabulations, and actor-based comparisons, while qualitative information from focus group discussions and key informant interviews was used to explain the institutional, market, and coordination issues behind the statistical patterns. The findings show that farmers mainly supplied processors (53.5%) and petty traders (46.5%), while processors sold largely to retailers (41.2%) and households (38.2%). Value addition was concentrated at the processing node, where 88.2% of processors sold both sunflower oil and sunflower cake, whereas all sampled farmers sold raw sunflower seed. Low market price was the most frequently reported marketing constraint, accounting for 42 responses, followed by unreliable markets with 34 responses and undeveloped productive infrastructure with 28 responses. These findings indicate that the chain is commercially active but weakly governed, with farmers having limited influence over prices, processors facing uncertain raw-material supply, and traders often benefiting from superior market information and cash capacity. The paper concludes that sunflower value-chain performance depends on strengthening collective marketing, transparent price setting, quality standards, aggregation, finance, and trust-based coordination among actors. It recommends institutional arrangements that connect production, processing, trading, and consumption more inclusively and competitively.